2023
DOI: 10.3389/fped.2023.1318690
|View full text |Cite
|
Sign up to set email alerts
|

Gender and authorship of publications from Pediatric Acute Lung Injury and Sepsis Investigators (PALISI)

Asumthia S. Jeyapalan,
Stephanie R. Brown,
Mary G. Gaspers
et al.

Abstract: IntroductionPediatric Acute Lung Injury and Sepsis Investigators (PALISI) is a network fostering clinical research to optimize care for critically ill children. We aim to examine the efforts of the PALISI Network to increase gender parity in research, as evidenced by authorship.MethodsThe first and senior authors of all published PALISI articles from 2002 to 2021 were analyzed for gender of presentation. Funding sources, impact factors, professional roles, and location were extracted.ResultsWe identified 303 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…On the other hand, a study investigating gender differences in the authorship of publications from Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) reported that the number of female first authors between 2012 and 2021 was considerably higher compared to the years between 2002 and 2011 (60.2% vs. 37.7%; p = 0.002). However, the proportion of female senior authors did not change over time [14].…”
Section: Trends In Gender Differencesmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, a study investigating gender differences in the authorship of publications from Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) reported that the number of female first authors between 2012 and 2021 was considerably higher compared to the years between 2002 and 2011 (60.2% vs. 37.7%; p = 0.002). However, the proportion of female senior authors did not change over time [14].…”
Section: Trends In Gender Differencesmentioning
confidence: 84%
“…FIGURE 3: A forest plot showing gender differences in senior authorshipOR: odds ratio; CI: confidence interval; M-H: Mantel-Haenszel[11][12][13][14][15][16][17] …”
mentioning
confidence: 99%